Creatine supplementation enhances muscle force recovery after eccentrically-induced muscle damage in healthy individuals - Cribb Paul J; Williams Andrew D; Rybalka Emma; Cooke Matthew B; Hayes Alan (Taylor & Francis Group, 2009)
Abstract Background Eccentric exercise-induced damage leads to reductions in muscle force, increased soreness, and impaired muscle function. Creatine monohydrate's (Cr) ergogenic potential is well established; however few studies have directly examined the effects of Cr supplementation on recovery after damage. We examined the effects of Cr supplementation on muscle proteins and force recovery after eccentrically-induced muscle damage in healthy individuals. Methods Fourteen untrained male participants (22.1 ± 2.3 yrs, 173 ± 7.7 cm, 76.2 ± 9.3 kg) were randomly separated into 2 supplement groups: i) Cr and carbohydrate (Cr-CHO; n = 7); or ii) carbohydrate (CHO; n = 7). Participants consumed their supplement for a period of 5 days prior to, and 14 days following a resistance exercise session. Participants performed 4 sets of 10 eccentric-only repetitions at 120% of their maximum concentric 1-RM on the leg press, leg extension and leg flexion exercise machine. Plasma creatine kinase (CK) and lactate dehydrogenase (LDH) activity were assessed as relevant blood markers of muscle damage. Muscle strength was examined by voluntary isokinetic knee extension using a Cybex dynamometer. Data were analyzed using repeated measures ANOVA with an alpha of 0.05. Results The Cr-supplemented group had significantly greater isokinetic (10% higher) and isometric (21% higher) knee extension strength during recovery from exercise-induced muscle damage. Furthermore, plasma CK activity was significantly lower (by an average of 84%) after 48 hrs (P < 0.01), 72 hrs (P < 0.001), 96 hrs (P < 0.0001), and 7 days (P < 0.001) recovery in the Cr-supplemented group. Conclusion The major finding of this investigation was a significant improvement in the rate of recovery of knee extensor muscle function after Cr supplementation following injury.